Acceptability Study on HIV Self-Testing among Transgender Women, Men who Have Sex with Men, and Female Entertainment Workers in Cambodia: A Qualitative Analysis. - Khuondyla Pal; Chanrith Ngin; Sovannary Tuot; Pheak Chhoun; Cheaty Ly; Srean Chhim; Minh-Anh Luong; Brent Tatomir; Siyan Yi (PLoS ONE, 2016)
In Cambodia, HIV prevalence is high while HIV testing rates remain low among transgender women (TG women), men who have sex with men (MSM), and female entertainment workers (FEW). Introducing self-testing for HIV to these key populations (KPs) could potentially overcome the under-diagnosis of HIV and significantly increase testing rates and receipt of the results, and thus could decrease transmission. Therefore, this study aimed to determine the acceptability of HIV self-testing (HIVST) among these three categories of KPs.This study was conducted through focus group discussions (FGDs) with TG women, MSM, and FEW in Phnom Penh city, Kampong Cham, Battambang, and Siem Reap provinces of Cambodia. Convenience sampling was used to recruit the participants. Two FGDs (six participants in each FGD) were conducted in each target group in each study site, totaling 24 FGDs (144 participants). Thematic analysis was performed to identify common or divergent patterns across the target groups.Almost all participants among the three groups (TG women, MSM, and FEW) had not heard about HIVST, but all of them expressed willingness to try it. They perceived HIVST as confidential, convenient, time-saving, and high-tech. Barriers to obtaining HIVST included cost, access, administration technique, embarrassment, and fear of pain. The majority preferred counseling before and after testing.Participants showed high willingness to use and acceptability of HIVST due to its confidentiality/privacy and convenience even if it is not linked to a confirmatory test or care and treatment. Notwithstanding, to increase HIVST, the target groups would need affordable self-test kits, education about how to perform HIVST and read results, assurance about accuracy and reliability of HIVST, and provision of post-test counseling and facilitation of linkage to care and treatment.